2018
DOI: 10.1038/s12276-018-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule natural compound agonist of SIRT3 as a therapeutic target for the treatment of intervertebral disc degeneration

Abstract: Oxidative stress-induced mitochondrial dysfunction is implicated in the pathogenesis of intervertebral disc degeneration (IVDD). Sirtuin 3 (SIRT3), a sirtuin family protein located in mitochondria, is essential for mitochondrial homeostasis; however, the role of SIRT3 in the process of IVDD has remained elusive. Here, we explored the expression of SIRT3 in IVDD in vivo and in vitro; we also explored the role of SIRT3 in senescence, apoptosis, and mitochondrial homeostasis under oxidative stress. We subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 34 publications
1
67
0
Order By: Relevance
“…To determine the causative role of expression levels of TRPS1, miR-221 and FOXO3 in driving disc degeneration or homeostasis, and to provide more prospects for therapeutic targets, in vivo strategies will be needed. Further studies are needed also to investigate possible relationships of these molecules with perturbations of Wnt/β-catenin, Notch, interferon-alpha, hypoxia, nuclear factor kappa B (NF-kB), Sirtuin 3 and mitogen-activated protein kinase (MAPK) pathways that have been identified as important regulators of progress of disc degeneration [7,44,45,46,47,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the causative role of expression levels of TRPS1, miR-221 and FOXO3 in driving disc degeneration or homeostasis, and to provide more prospects for therapeutic targets, in vivo strategies will be needed. Further studies are needed also to investigate possible relationships of these molecules with perturbations of Wnt/β-catenin, Notch, interferon-alpha, hypoxia, nuclear factor kappa B (NF-kB), Sirtuin 3 and mitogen-activated protein kinase (MAPK) pathways that have been identified as important regulators of progress of disc degeneration [7,44,45,46,47,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was done to NP cells according to previous descriptions [ 36 ]. Primary antibodies aiming at cleaved caspase-3 (1: 400; #9579, Cell Signaling Technology) were first used to incubate with NP cells at 4°C for all night.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that honokiol upregulates Drp-1 and Mfn-2 and increases mitophagy in the sirtuin 3-dependent manner [114] TBHP-treated NP cells, AF-punctured rat model Anti-apoptotic, preserved ECM homeostasis via mitophagy induction both in vitro and in vivo [115] IL-1β-treated NP cells Attenuated NLRP3 inflammasome activation, decreased mtROS level [116] ALA (206. Accelerated aging ERCC1 −/Δ mouse model Ameliorated IVD degeneration, enhanced disc ECM content [59] which was determined by upregulation of BNIP3 and the ratio of LC3-II to LC3-I [139].…”
Section: Non-canonical Pathwaymentioning
confidence: 99%